REINTERPRETASI GERAKAN DAKWAH FRONT PEMBELA ISLAM (FPI) - machfud syaefudin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2014)
Front Pembela Islam (FPI) is an Islamic socio-religious organization group in Indonesia. The members’ preaching ways are considerably radical, and often has appalled many people, especially in implementing “amar ma’ruf nahi munkar”. These radical actions have caused some fear, even violated human rights for some members of the community. This study, then, presents the facts by looking further interactions and implications of FPI’s social movement in da’wah activities. Thus, the symbol and propaganda on “amar ma’ruf nahi munkar” are possibly reconsidered based on the social conditions of surrounding communities. Taking an action as a law enforcer of values, norms, and social order in the community means neglecting the responsibility of the government.***Front Pembela Islam (FPI) adalah sebuah kelompok organisasi sosial keagamaan Islam di Indonesia. Cara berdakwah para anggota FPI yang radikal, sering menimbulkan terkejut banyak orang, terutama dalam menerapkan